Failure analysis of ICDP work roll of hot strip mill case study of shell-core interface spalling - Setiawan, Ridwan; Siradj, Eddy S; Iman, Fauzul (Universitas Negeri Padang, 2022)
The failure of the roll during the rolling process causes cobble to lose production time for several hours. Investigations include visual inspection, lltrasonic test, chemical analysis, metallography, and hardness measurement. Stand finishing F1-F4 uses High Chrome (HCr) material type, while Stand F5-F6 uses ICDP material type. Spalling work roll occurs on stand F5 with Roll Top position. Roll was chipped between shell and core with an exfoliation percentage of 30% of the roll surface area. Visually, the chipped part looks smooth and even. Thus no typical sign of fatigue or brittle failure was observed. The chemical composition of the roll conforms to the standard. Roll surface hardness that does not experience spalling follows the standard. The metallography analysis found micro-cracks in the spalled samples and inclusions in the form of scale in the shell-core interface. Based on the study, it can be concluded that the spalling roll is caused by poor bonding of the shell and core on the roll.